Discovery of Novel Chemical Series of OXA-48 β-Lactamase Inhibitors by High-Throughput Screening - Barbara Garofalo; Federica Prati; Rosa Buonfiglio; Isabella Coletta; Noemi D'Atanasio; Angela Molteni; Daniele Carettoni; Valeria Wanke; Giorgio Pochetti; Roberta Montanari; Davide Capelli; Claudio Milanese; et al. (MDPI AG, 2021)
The major cause of bacterial resistance to β-lactams is the production of hydrolytic β-lactamase enzymes. Nowadays, the combination of β-lactam antibiotics with β-lactamase inhibitors (BLIs) is the main strategy for overcoming such issues. Nevertheless, particularly challenging β-lactamases, such as OXA-48, pose the need for novel and effective treatments. Herein, we describe the screening of a proprietary compound collection against Klebsiella pneumoniae OXA-48, leading to the identification of several chemotypes, like the 4-ideneamino-4H-1,2,4-triazole (SC_2) and pyrazolo[3,4-b]pyridine (SC_7) cores as potential inhibitors. Importantly, the most potent representative of the latter series (ID2, AC50 = 0.99 μM) inhibited OXA-48 via a reversible and competitive mechanism of action, as demonstrated by biochemical and X-ray studies; furthermore, it slightly improved imipenem's activity in Escherichia coli ATCC BAA-2523 β-lactam resistant strain. Also, ID2 showed good solubility and no sign of toxicity up to the highest tested concentration, resulting in a promising starting point for further optimization programs toward novel and effective non-β-lactam BLIs.